Sizzle : a novel - Garwood, Julie (New York : Ballantine Books, 2009)
Accidentally leaving her camera running while filming a documentary in the hills of Los Angeles, Lyra Prescott inadvertently records a shocking crime and finds herself targeted by the killer, a situation for which attractive FBI agent Ben Kincaid is dispatched to protect her.
Keywords: Romantic suspense fiction